Mapping The Evolution of Customer Experience Management Research in Indonesia - Lefrand S. Pasuhuk; Sandra J. R. Kainde; Deske W. Mandagi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Customer Experience Management (CEM) has emerged as a critical strategic paradigm for enhancing customer satisfaction, strengthening loyalty, and sustaining competitive advantage in increasingly digital and experience-driven markets. This study conducts a systematic literature review (SLR) to map the evolution, intellectual structure, and thematic development of CEM research in the Indonesian context. Following the PRISMA framework, 210 records were initially retrieved from the Scopus database, yielding a final sample of 67 peer-reviewed journal articles published between 2010 and 2025. Bibliometric and keyword co-occurrence analyses reveal four dominant research clusters: customer experience and relationship management; brand management and brand equity development; digital and technology-enabled marketing; and sales performance and market-driven strategy. The findings indicate that Indonesian CEM research has evolved from traditional service quality and satisfaction perspectives toward more integrated, experience-centric, and digitally enabled frameworks. Despite this progress, several areas remain underexplored, including emotional and psychological dimensions of customer experience, advanced analytics and artificial intelligence integration, ethical and cultural considerations, and the development of robust, context-sensitive experience measurement frameworks. By synthesizing fragmented research streams into a coherent thematic structure, this study offers theoretical insights into the maturation of CEM research. It provides a foundation for advancing future scholarship and managerial practice in Indonesia and similar emerging market contexts.